Medication-Overuse Headache (Review of Literature and Recommendations for Practice) - N. L. Starikova (SINAPS LLC, 2023)
Medication-overuse headache (MOH) is a highly prevalent secondary headache, developing in patients with frequent and chronic cephalalgias due to excessive use of "acute" medications for headache, and significantly affecting patients' quality of life. Treatment of MOH demands high compliance physician-patient, and the result is satisfactory not in all cases. For this reason, the prophylaxis of overuse of symptomatic medications for headaches is important. The review presents contemporary data on MOH, its treatment and prophylaxis.